Sufi Government Approach for Prevention of Corruption in Bureaucracy (Study in Malang City Government) - Rochmah, Siti; Trisnawati, Trisnawati; Lastiti, Niken (International Journal of Social and Local Economic Governance, 2017)
Indonesian bureaucracy reform has been widely conducted since 1997. However, the reform is still not able to fix the bureaucratic corruption culture. This paper proposes sufi government approach as an alternative approach to reform corruptive culture within Indonesia’s bureaucracy. This study used a qualitative research approach. The use of qualitative research methods is aimed to describe and analyze the phenomenon of development of personnel resources in a sufi government perspective related to the prevention of corruption by bureaucrats concerning three issues. Result or finding of t this research is sufi government as an approach relies on true monotheism which is used to strengthen internal control system in poor bureaucracy contexts. The basic argument in this approach is that monotheism is true and therefore bureaucrats in charge of serving the community should carry out their duties in a comprehensive manner. As which ones have been listed in the code of ethics of the bureaucracy. In this approach, bureaucrats should see the task as a trust rather than a means to accumulate wealth and depriving the people they serve. Keywords: Sufi Government, corruption, bureaucracy